PENGEMBANGAN E-MODUL DENGAN PENDEKATAN RME UNTUK MENDUKUNG KEMAMPUAN LITERASI MATEMATIS SISWA SMP/MTs - Vina Rohmatika; Khaerunnisa, Etika; Rafianti, Isna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this research is to determine the levels of validity, practicality, and effectiveness of an e-module using the Realistic Mathematics Education (RME) approach to support the mathematical literacy skills of junior high school (SMP/MTs) students on the topic of systems of linear equations with two variables. This study is a type of development research (research and development) employing the ADDIE model. The validation results indicate that the content experts achieved a percentage score of 92% in the "Very Valid" category, while the media experts obtained 89% in the "Very Valid" category. Teacher responses yielded a percentage score of 89% in the "Very Practical" category, and student responses resulted in 86% in the "Very Practical" category. Furthermore, the analysis of pretest and posttest data produced an N-Gain score of 0.63 in the "Medium" category, with an N-Gain percentage of 63% classified as "Quite Effective." Based on the research findings, it can be concluded that the e-module with the RME approach to support mathematical literacy skills of SMP/MTs students on systems of linear equations with two variables is valid, practical, and effective for use as teaching material in Grade VIII at SMPN 1 Pabuaran.